Mesenchymal stem cells under hypoxia condition inhibit peritoneal adhesion by suppressing the prolonged release of interleukin-6 - Adi Muradi Muhar; Agung Putra; Vito Mahendra Ekasaputra; Dewi Masyithah Darlan; Desiree Anggia Paramita; Iqbal Pahlevi Adeputra Nasution (Medicinski glasnik, 2021)
Aim: To investigate the role of hypoxia-preconditioned mesenchymal stem cells (H-MSCs) in preventing peritoneal adhesion by regulating IL-6 at days 6 and 12. Methods: Twenty-four PAs rat model weighing 250 g to 300 g were randomly allocated into 4 groups: sham (Sh), control (C), H-MSCs treatment group at dose 1.5 x 106 (T1) and 3 x 106 (T2). To induce H-MSCs, all MSCs population were incubated under hypoxia state (5% O2), 5% CO2, and 37o C for 24 hours. Expression level of IL-6 was performed using ELISA. Morphological appearance of adhesion was observed by visualizing the existence of adhesion formation in intestinal. Results: In this study we found that there was a trend of decrease of IL-6 level on day 6 following MSCs treatments. Interestingly, there was a significant decrease of IL-6 level on day 12 in all treatment groups. Also, no adhesion occurred in T2 group. Conclusions: H-MSCs prevent PA development by suppressing the prolonged release of IL-6 at proliferation phase.
Keywords: abdominal pain; abdominal surgery; cellular; inflammatory cytokines